Bush on the home front : domestic policy triumphs and failures - Graham, John D. (Indiana University Press, 2010)
"Military operations in Afghanistan and Iraq consumed so much attention during his presidency that few people appreciated that George W. Bush was also an activist on the home front. Despite limited public support, and while confronting a deeply divided Congress, Bush engineered and implemented reforms of public policy on a wide range of issues: taxes, education, health care, energy, environment, and regulatory reform. In Bush on the Home Front, former Bush White House official and academic John D. Graham analyzes Bush's successes in these areas and setbacks in other areas such as Social Security and immigration reform. Graham provides valuable insights into how future presidents can shape U.S. domestic policy while facing continuing partisan polarization."--Jacket.